A Comparative Analysis of the Protection of Trade Names Under the English Tort of Passing Off and Section 18 of Thailand's Civil and Commercial Code. Issue 1 (30th May 2016) - REEKIE, Surutchada; REEKIE, Adam
Abstract: The English common law tort of passing off came into the spotlight in 2015 with the UK Supreme Court case of Starbucks (HK) Ltd v British Sky Broadcasting Group settling the current position regarding the question of the territorial scope of goodwill. This article undertakes a comparative study of the tort with Section 18 of the Thai Civil and Commercial Code which, it argues, has been interpreted by the Thai Supreme Court to offer a materially similar remedy to the English tort in two important conceptual aspects: the requirement for misrepresentation and the so-called "hard line" approach to the territorial scope of goodwill, as affirmed by Starbucks . The analysis carries important implications for comparative lawyers and legislators in both the UK and Thailand, and challenges assumptions based on a simplistic categorization of Thailand as a civil law jurisdiction.